The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41416-019-0603-6
|View full text |Cite
|
Sign up to set email alerts
|

Circulating biomarkers in patients with glioblastoma

Abstract: Gliomas are the most common tumours of the central nervous system and the most aggressive form is glioblastoma (GBM). Despite advances in treatment, patient survival remains low. GBM diagnosis typically relies on imaging techniques and postoperative pathological diagnosis; however, both procedures have their inherent limitations. Imaging modalities cannot differentiate tumour progression from treatment-related changes that mimic progression, known as pseudoprogression, which might lead to misinterpretation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
128
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(150 citation statements)
references
References 136 publications
(217 reference statements)
1
128
0
Order By: Relevance
“…Regulation of EV release is critical for cellular communication and modulation of the microenvironment in cancer progression and metastasis and recognised to be of increasing importance in GBM [21,22]. GBM-derived EVs have furthermore been shown to induce tumour-promoting transformation of subventricular zone resident neural stem cells, possibly contributing to GBM recurrence [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of EV release is critical for cellular communication and modulation of the microenvironment in cancer progression and metastasis and recognised to be of increasing importance in GBM [21,22]. GBM-derived EVs have furthermore been shown to induce tumour-promoting transformation of subventricular zone resident neural stem cells, possibly contributing to GBM recurrence [64].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are recognised players in mediating such changes, being lipid bilayer-enclosed structures, 30-1000 nm in diameter, released from cells and acting as key-mediators for intra/inter-tumour communication through horizontal transfer of functional proteins and nucleic acids (mRNA, miRNA, lncRNA, sncRNA) [17][18][19][20]. EVs have great potential as diagnostic and prognostic biomarkers in a range of pathologies, including GBM, and therefore increased understanding of EV-mediated functions in GBM biology is urgently needed [21,22]. In GBM, EV protein-cargo has for example been associated with the phenotypic signature of GBM cells [23], while TMZ treatment has been shown to increase EV release in GBM and to promote more pro-oncogenic EV signatures [24].…”
Section: Introductionmentioning
confidence: 99%
“…The current treatment of GBM includes a combination of surgery, radiotherapy and chemotherapy, and the standard chemotherapy drug in use is temozolomide (TMZ). Nevertheless, on account of the high drug resistance rate to treatment and recurrence rate of GBM patients, the overall survival is poor, with only a median survival period of about 15 months (26). Hence, the novel therapeutic target and treatment strategy should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the proteomic profiling of these EVs showed a glioblastoma-specific pattern with EGFR amplifications, PTEN deletions, IDH1/2, and TP53 mutations [ 73 ]. In another study, it was found that syndecan-1 present in plasma EVs can be useful to distinguish low-grade from high-grade glioma with a sensitivity of 71% and a specificity of 80% [ 74 ]. Certain miRNAs, as it was demonstrated for example by Ebrahimkhani et al, are selectively packaged into exosomes regulating cell proliferation in glioma.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%